2009
DOI: 10.1073/pnas.0907655106
|View full text |Cite
|
Sign up to set email alerts
|

Evolution amplified processing with temporally dispersed slow neuronal connectivity in primates

Abstract: The corpus callosum (CC) provides the main route of communication between the 2 hemispheres of the brain. In monkeys, chimpanzees, and humans, callosal axons of distinct size interconnect functionally different cortical areas. Thinner axons in the genu and in the posterior body of the CC interconnect the prefrontal and parietal areas, respectively, and thicker axons in the midbody and in the splenium interconnect primary motor, somatosensory, and visual areas. At all locations, axon diameter, and hence its con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
203
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 176 publications
(241 citation statements)
references
References 20 publications
(20 reference statements)
35
203
0
2
Order By: Relevance
“…In the monkey, the delays from prefrontal cortex are 3.4 ms for the ipsilateral (Innocenti et al 2013) and 5.1 ms for the contralateral projection to n caudatus (this paper). By taking into account an increase in axon diameters in humans in the order of 30% (compatible with macaque/human comparative data; Caminiti et al 2009) and of conduction distance proportional to the cubic route of brain volumes, validated by DT tracing (Caminiti et al 2009) the ipsi-and contra-calculated values in humans are 6.6 and 9.9 ms ( Table 2). This means an average difference of 3.3 ms between the ipsilateral and the contralateral projection.…”
Section: Diameter Of Axons and Conduction Delayssupporting
confidence: 54%
See 4 more Smart Citations
“…In the monkey, the delays from prefrontal cortex are 3.4 ms for the ipsilateral (Innocenti et al 2013) and 5.1 ms for the contralateral projection to n caudatus (this paper). By taking into account an increase in axon diameters in humans in the order of 30% (compatible with macaque/human comparative data; Caminiti et al 2009) and of conduction distance proportional to the cubic route of brain volumes, validated by DT tracing (Caminiti et al 2009) the ipsi-and contra-calculated values in humans are 6.6 and 9.9 ms ( Table 2). This means an average difference of 3.3 ms between the ipsilateral and the contralateral projection.…”
Section: Diameter Of Axons and Conduction Delayssupporting
confidence: 54%
“…The third (M93-80) from the Cognition Center, University of Fribourg, was a male of 4 years of age (4.5 kg body weight). Other connections of the first 2 monkeys were published (Caminiti et al 2009;Tomasi et al 2012;Innocenti et al 2013) and the methods reported therein. Briefly, surgery was performed by a professional human neurosurgeon under strict sterile conditions.…”
Section: Histologymentioning
confidence: 99%
See 3 more Smart Citations